Isolated Unilateral Nasal Ala Cleft: A Rare Case Report - Sanghani, Rohit V.; Dhatric, Ramya Smruthi (Journal of Fetal Medicine, 2025)
Craniofacial clefts other than cleft lip and palate are reported to occur in 1.4 to 4.9 per 100,000 live births. Isolated cleft of the nasal ala is very rare, accounting for about 0.7% of all facial clefts. Prenatal diagnosis plays a critical role in management and parental counseling. In this case report, we present the diagnosis of an isolated unilateral cleft of the right nasal ala identified during the routine mid-trimester anomaly scan and confirmed through postnatal follow-up. The goal is to educate fetal medicine specialists about this rare diagnosis and to prevent postbirth surprises.
Keywords: counselling of parents; nasal ala cleft; prenatal diagnosis; reconstruction and grafting; routine mid trimester anomaly scan